Diabetic Schwann cells suffer from nerve growth factor and neurotrophin‐3 underproduction and poor associability with axons. Issue 12 (7th October 2013) - Dey, Indranil; Midha, Nisha; Singh, Geeta; Forsyth, Amanda; Walsh, Sarah K.; Singh, Bhagat; Kumar, Ranjan; Toth, Cory; Midha, Rajiv
<x xml:space="preserve">Abstract</x> Schwann cells (SCs) are integral to peripheral nerve biology, contributing to saltatory conduction along axons, nerve and axon development, and axonal regeneration. SCs also provide a microenvironment favoring neural regeneration partially due to production of several neurotrophic factors. Dysfunction of SCs may also play an important role in the pathogenesis of peripheral nerve diseases such as diabetic peripheral neuropathy where hyperglycemia is often considered pathogenic. In order to study the impact of diabetes mellitus (DM) upon the regenerative capacity of adult SCs, we investigated the differential production of the neurotrophic factors nerve growth factor (NGF) and neurotrophin‐3 (NT3) by SCs harvested from the sciatic nerves of murine models of type 1 DM (streptozotocin treated C57BL/6J mice) and type 2 DM (LepR−/− or db/db mice) or non‐diabetic cohorts. In vitro, SCs from diabetic and control mice were maintained under similar hyperglycemic and euglycemic conditions respectively. Mature SCs from diabetic mice produced lower levels of NGF and NT3 under hyperglycemic conditions when compared to SCs in euglycemia. In addition, SCs from both DM and non‐DM mice appear to be incapable of insulin production, but responded to exogenous insulin with greater proliferation and heightened myelination potentiation. Moreover, SCs from diabetic animals showed poorer association with co‐cultured axons. Hyperglycemia had significant impact upon SCs, potentially contributing to the pathogenesis of diabetic peripheral neuropathy. GLIA 2013;61:1990–1999